2019
DOI: 10.12681/jhvms.16128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GnRH or hCG on day 11 after artificial insemination in cows luteal activity

Abstract: In order to optimize luteal function by human chorionic gonadotrophin (hCG)  or gonadotrophin releasing hormone (GnRH) on day 11 after artificial insemination (AI). 33 cows synchronized by the Ovsynch and divided into 3 groups according to the type of treatment: 1) hCG (1500 IU, n=11); 2) GnRH (100 µg, n=11); and 3) control (2 mL of saline, n=11). Blood samples were collected from all animals every 3 days from day 5 to day 23 to determine progesterone concentration. Ultrasonography was used to monitor the lute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…Also, in cattle, hCG treatment on day 5 or 7 post-AI increased P4 level by enhancing P4 secretion from the existing CL [29,62]. Contrary, total and principle CL areas were significantly higher on days 20 and 23 in hCGtreated cows compared to GnRH and control groups [10]. Also, the present finding is contrasted by the observation of an increase of CL area in hCG-treated cows compared with GnRH-treated cows with a strong positive and close correlation between the total luteal area and P4 level in GnRH group and previous studies [24].…”
Section: Average CL Diameter On Different Post-mating Daysmentioning
confidence: 85%
“…Also, in cattle, hCG treatment on day 5 or 7 post-AI increased P4 level by enhancing P4 secretion from the existing CL [29,62]. Contrary, total and principle CL areas were significantly higher on days 20 and 23 in hCGtreated cows compared to GnRH and control groups [10]. Also, the present finding is contrasted by the observation of an increase of CL area in hCG-treated cows compared with GnRH-treated cows with a strong positive and close correlation between the total luteal area and P4 level in GnRH group and previous studies [24].…”
Section: Average CL Diameter On Different Post-mating Daysmentioning
confidence: 85%
“…Poncio et al (2015) reported a pregnancy rate of 38.8% using GnRH-based protocols in 49 Nelore heifers for 24 months in the southeastern region of the state of São Paulo. Superior results were described by Besbaci et al (2018), who identified a pregnancy rate of 45.45% in GnRH-based hormonal protocols in Algeria. Uslenghi et al (2016), evaluating different protocols, found a GnRH pregnancy rate of 47.9%.…”
Section: Resultsmentioning
confidence: 89%
“…Poncio et al (2015) sinalizaram uma taxa de prenhez de 38,8% utilizando protocolos à base de GnRH em 49 novilhas nelores, que possuíam idade equivalente a 24 meses, na região sudeste no estado de São Paulo. Resultados superiores foram descritos por Besbaci et al (2018), que identificaram taxa de prenhez de 45,45% em protocolos hormonais à base de GnRH, na Argélia. Já Uslenghi et al (2016) avaliando diferentes protocolos, constataram taxa de prenhez de GnRH de 47,9%.…”
Section: Resultsunclassified